Scaling digital tools for banana agronomy and diseases prevention in Rwanda - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
ICT4BXW project developed digital tools for banana management and disease control, mainly the Banana Xanthomonas Wilt (BXW) disease. The tools are supporting banana extension agents and decision-makers in diagnosing the BXW disease and applying control measures wherever necessary.